Evaluating the impact of sales methods on profitability in the Japanese software industry - Takaaki Ishikawa; Kiminori Gemba (Innovative Marketing)
This study aims to examine the impact of sales channels, either direct or indirect, on the profitability of software companies in Japan, and to further elucidate the differences in international competitive advantages by comparing Japanese firms with U.S. SaaS companies. This study analyzes the financial data of Japanese software manufacturers listed on the Tokyo Stock Exchange over the three-year period from 2020 to 2022. Companies are classified into direct sales and indirect sales groups based on their revenue and operating profit margins. Additionally, Welch’s t-test was performed to compare the profitability of these companies, and comparisons were also made with U.S. Software-as-a-Service (SaaS) companies. The analysis revealed that Japanese companies adopting indirect sales channels exhibited statistically significantly higher profitability than those using direct sales channels (t = 2.3828, p = 0.0263, mean difference = 0.1701). Moreover, Japanese companies with indirect sales channels also demonstrated significantly higher profitability when compared to U.S. SaaS companies (t = 4.7911, p = 0.00001, mean difference = 0.3874). These findings suggest that, particularly in the small and medium-sized enterprise (SME) market, the use of indirect sales channels effectively bridges the IT literacy gap and enhances profitability. This study concludes that indirect sales channels serve as a strategic factor that strengthens the competitive advantage of Japanese software companies and contributes to the improvement of profitability.